THE BUDDHIST PSYCHOLOGICAL PROCESSES INFLUENCING FAITH IN BUDDHISM AMONG THE PEOPLE OF KUSHINAGAR, UTTAR PRADESH, INDIA - (Songkran Kittiwangso), PhrakruVajirabodhivides; Srikhruedong, Siriwat; Ragkhanto, Suwatsan; Mererk, Sayyud; Vachirapanyo, PhrasamuChokdee (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims to 1) study the faith in Buddhism of Indians, 2) develop the process of Buddhist psychology that affects the faith in Buddhism of Indians, and 3) present the process of Buddhist psychology that affects the faith in Buddhism of Indians. This qualitative research consisted of interviews with 15 key informants, divided into Buddhist religious leaders in India, namely the head of the Thai Dharma Missionary Mission in India-Nepal and the abbot of a Buddhist temple in Kusinagara, India, and Indian Buddhists. A focus group discussion was held with 11 qualified persons. Data were analyzed using content analysis. The research results found that 1) the faith in Buddhism of Indians was divided into 2 types: social faith and religious faith. 2) The development of the process of Buddhist psychology that affected the faith in Buddhism of Indians was as follows: (1) The principle of the process of Buddhist psychology that affected the faith in Buddhism of Indians. The principle of faith of Indians came from the experience of perception from the senses and the perception of emotions. (2) The method of the process of Buddhist psychology that affected the faith in Buddhism of Indians consisted of holding the limit, listening to the sound from outside, thinking by oneself. (3) The results of Buddhist psychological processed affecting the faith in Buddhism of Indians included Indians having the right way of life and not clinging to and abandoning desires, cultivating mindfulness and having the determination to practice to escape suffering. And 3) The Buddhist psychological processed affecting the faith in Buddhism of Indians included (1) holding limits, (2) listening to external sounds, (3) thinking for oneself, and (4) practicing for oneself in order to create good relationships among religious people, religious leaders and communities, and strengthening religion and people's faith.